Risk of Depression Among Stroke Patients with Obstructive Sleep Apnea: A Prospective Cohort Study - Wahab, Abdul; Tariq, Wasim; Siddiqui, Maimoona; Sayem Ul Haque, (Indus Journal of Bioscience Research, 2025)
Background: Stroke survivors frequently worry about sleep disturbance, but it is still unclear how long people sleep for and if obstructive sleep apnea is linked to depression after stroke and mortality from all causes and cardiovascular disease. Our goal was to investigate these connections. Study Design: prospective cohort study. Settings: Department of Neurology, Shifa International Hospital, Islamabad. Study duration: February 2025 to April 2025. Methods: Included were adults who had survived stroke. Self-reports on pertinent questionnaires were used to obtain data on sleep and stroke diagnoses. Data on mortality were gathered. To investigate these relationships and determine the odds ratio (OR) and hazard ratio (HR), respectively, multivariate logistic regression and Cox proportional hazards regression were employed. Results: There were 173 stroke participants in all. Obstructive sleep apnea was linked to higher risks of depression after stroke in the fully adjusted model (OR 2.689, p = 0.0146). The likelihood of depression after stroke was inversely correlated with sleep duration; short sleep duration was linked to higher odds of depression after stroke (OR 2.196, p = 0.0059) than long sleep duration (p = 0.1445). Conclusions: Short sleep duration and obstructive sleep apnea were linked to higher chances of depression after stroke. These results highlight how correcting sleep disturbances and attaining a normal sleep duration may lower the risk of depression after stroke and death.